The impact of the Great War on women in Ireland, 1914 - 1919 - Walsh, Fionnuala (Trinity College (Dublin, Ireland). Department of History, 2016)
The impact of the Great War on women is a significant area of scholarship within First World War studies. The legacy of the war for women's lives and role in society has been the subject of much debate. This thesis investigates the extent to which the war affected women's lives in Ireland. It aims to demonstrate the socio-economic, psychological and political impact of the Great War upon Irishwomen. Thousands of Irishwomen participated in voluntary work to support the war effort, gained new employment opportunities or were affected by the military service of a loved one. However, although there has been a surge in studies examining Irish military involvement in the war in the last two decades, there has been no systematic study of the impact of the war on women's lives.
Embargo End Date: 2022-01-01
Keywords: Histories & Humanities, Ph.D.; Ph.D. Trinity College Dublin, 2016